The effect of removing visual information on reach control in young children. - Babinsky, E; Braddick, O; Atkinson, J (2012)
Visual information about the hand, the reach space, and a target can all contribute to the control of a reaching movement. When visual information is removed, both feedforward mechanisms (involved in planning the movement) and feedback mechanisms (involved in correcting errors) may be affected. This study looks at how 4- to 5-year-old children use visual information to guide reaching movements. Children reached for a toy object in four conditions--in the light, in the dark while the toy was glowing, and in complete darkness after a 0-s delay and a 4-s delay. When a reach in the glowing condition was compared with a reach in the light, reaches were more curved, had a longer duration, and earlier time-to-peak-velocity than a reach in the light but the number of grasping responses were comparable to in the light condition. When a reach in the two dark conditions (0- and 4-s) was compared with a reach in the light, the number of grasping responses decreased and 14 and 31 % of reaches resulted in a miss, that is, no contact was made with the object. While we did not find any significant kinematic differences between the 0- and 4-s dark conditions, there was a significantly larger number of misses in the 4-s dark condition, suggesting that memory of target position may decay over time. Overall, removing vision of the hand and reach space in the glowing condition appears to affect the planning of a reach (as vision of the hand was not available at reach initiation) and feedback control, while removing vision of the object in the dark conditions has an effect on endpoint response as we found that children experience difficulty retrieving the object in the dark. While young children demonstrate more adult-like reach control (i.e., relatively longer deceleration time, increased reach duration) under reduced feedback conditions, they have difficulty retrieving the object in the dark, particularly after a 4-s delay, and it is possible that mechanisms guiding predictive control and visual memory are still developing.